Barriers to Treatment Access for Chagas Disease in Mexico - Manne-Goehler, Jennifer; Bärnighausen, Till (PLoS neglected tropical diseases, 2013)
Author Summary Chagas disease is a vector-borne disease caused by the parasite Trypanosoma cruzi. The disease is most frequently transmitted by triatomine insects but can also be passed through blood donation or from mother to child at birth. Experts estimate that 8 million people are infected with Chagas disease globally and that 1.1 million of these infections are found in Mexico. Most public health programs for Chagas disease focus on preventing new infections through vector control and screening the blood supply. However, in recent years there has been a greater focus on treating the disease with one of two available medications, benznidazole or nifurtimox. This study explores access to these two drugs in Mexico. The study shows that less than 0.5% of those who are infected with the disease received treatment in Mexico in years. The study also identified important factors that limit access in Mexico, including the exclusion of both drugs from the national health insurance program and problems importing these medications. Finally, the paper suggests ways that these problems can be overcome in Mexico, while providing helpful insight for other countries that struggle with similar problems in treating this disease.
Gesehen am 19.01.2018